Dialog Dan Kerjasama Antar Umat Beragama Dalam Menciptakan Moderasi Dalam Perspektif Alkitab - Wahyuni , Sri; Pieter, roy (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
Religious moderation is a way to ensure the creation of harmony among different religious communities in this world. Without prioritizing or discriminating against any particular religion. The purpose of interfaith dialogue and cooperation is to maintain and create religious moderation for dialogue and mutual visits among religious leaders. This is a necessity in the field (the urgency of religion) to build and foster brotherhood, and to appreciate the existing differences. The basic principle of religious moderation is fairness and balance. The foundation for religious moderation from the biblical perspective that the author offers is based on Jeremiah 29:1-9; Romans 13:1-7. The church, in this case, the servants of God and Christians (believers), obeys the existing government. Pray and strive for the welfare of the city where God has placed us. For the welfare of the city is our collective welfare. The current government is an instrument that God uses for the good of society, the nation, and the country. The aim of this research is to foster harmony among religious communities and to fulfill their rights and obligations. The method used in this research is qualitative, utilizing supporting references through a literature approach.